Evaluating the use of hypoxia sensitive markers for body fluid stain age prediction. Issue 1 (December 2019) - Asaghiar, Fisal; Williams, Graham
Abstract: In order to augment DNA profiling and body fluid identification techniques, efforts are being made to increase the amount of information available from a crime scene stain, which includes efforts to identify externally visible characteristics through phenotypic analysis. A key question surrounding crime scene stains is the length of time between deposition of the stain and its subsequent recovery, in that is the stain recovered related to the incident in question or from a previously deposited stain number of weeks earlier? The inability to answer this fundamental question has a detrimental effect upon the successful completion of a criminal investigation. Once a body fluid leaves the body, the oxygen concentration in the environment changes, therefore it may be that this change could cause a change in expression of hypoxia-sensitive biomarkers. Here, a range of blood, saliva and semen samples were collected at 0 days, 7 days, 14 days, 21 days and 28 days of degrading at room temperature, before undergoing total RNA extraction and cDNA synthesis. All samples then underwent quantitative PCR targeting Vascular Endothelial Growth Factor A (VEGFA) and Hypoxia-Inducible Factor 1 Alpha (HIF1A), with B-Actin (ACTB) as a reference gene. A range of linear and quadratic correlation values was obtained from the qPCR data and used to develop a predictive model with a mean absolute deviation (MAD) of 5.3, 2.0, and 4.3 days for blood, saliva, and semen respectively. Blind testing indicated that a stain age prediction model based upon VEGFA with ACTB as a reference gene could be used on stains up four weeks old with a margin of error ranging from 2 days through to 5 days. Whilst a large potential time frame exists using this model, this represents a major step towards the target of having an accurate stain age prediction model.